Anodic Nanotubular/porous Hematite Photoanode for Solar Water Splitting: Substantial Effect of Iron Substrate Purity - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Killian, Manuela; Schmuki, Patrik (ChemSusChem, 2014)
Anodization of iron substrates is one of the most simple and effective ways to fabricate nanotubular (and porous) structures that could be directly used as a photoanode for solar water splitting. Up to now, all studies in this field focused on achieving a better geometry of the hematite nanostructures for a higher efficiency. The present study, however, highlights that the purity of the iron substrate used for any anodic-hematite-formation approach is extremely important in view of the water-splitting performance. Herein, anodic self-organized oxide morphologies (nanotubular and nanoporous) are grown on different iron substrates under a range of anodization conditions, including elevated temperatures and anodization supported by ultrasonication. Substrate purity has not only a significant effect on oxide-layer growth rate and tube morphology, but also gives rise to a ninefold increase in the photoelectrochemical water-splitting performance (0.250 vs. 0.028mA cm-2 at 1.40V vs. reversible hydrogen electrode under AM1.5 100mW cm-2 illumination) for 99.99 % versus 99.5 % purity iron substrates of similar oxide geometry. Elemental analysis and model alloys show that particularly manganese impurities have a strong detrimental effect on the water-splitting performance.
EAM Import::2019-03-13

A significant cathodic shift in the onset potential of photoelectrochemical water splitting for hematite nanostructures grown from Fe-Si alloys - Wang, Lei; Lee, Chong-Yong; Kirchgeorg, Robin; Hildebrand, Helga; Müller, Julian; Spiecker, Erdmann; Schmuki, Patrik (Materials Horizons, 2014)
Thermal oxidation of Fe to nanostructured hematite (wires, flakes) is currently widely investigated to produce efficient photoanodes for photoelectrochemical water splitting. The process carried out on pure iron, however, has the key drawback that not only hematite but a layered structure of Fe2O3-Fe3O4-FeO is formed where the thick suboxide layer underneath the Fe2O3 is highly detrimental to the photoresponse. In the present work, we show that suboxide formation can be largely suppressed if hematite nanowires/nanoflakes are thermally grown on Fe-Si alloys. For hematite structures grown on a Fe-Si alloy with 5 at% Si, a photocurrent onset potential as low as 0.6 V-RHE can be reached (under AM 1.5 illumination and 1 M KOH). We believe that the results represent a key finding towards the formation of optimized hematite nanostructures using a thermal oxidation method.

Enhanced Photoelectrochemical Water Splitting Efficiency of a Hematite-Ordered Sb:SnO2 Host-Guest System - Wang, Lei; Palacios-Padros, Anna; Kirchgeorg, Robin; Tighineanu, Alexei; Schmuki, Patrik (ChemSusChem, 2014)
Host–guest systems such as hematite/SnO2 have attracted a great deal of interest as photoanodes for photoelectrochemical water splitting. In the present work we form an ordered porous tin oxide layer formed by self-organizing anodization of Sn films on a FTO substrate. Subsequently the anodic tin oxide nanostructure is doped with antimony (ATO) by a simple impregnation and annealing treatment, and then decorated with hematite using anodic deposition. Photoelectrochemical water splitting experiments show that compared to conventional SnO2 nanostructures, using a Sb doped nanochannel SnO2 as a host leads to a drastic increase of the water splitting photocurrent response up to 1.5mA cm-2 at 1.6V (vs. RHE) in 1 M KOH under AM 1.5 (100mW cm-2) conditions compared to 0.04mA cm-2 for the non-Sb doped SnO2 scaffold.
EAM Import::2019-03-14

Enhancing the Water Splitting Efficiency of Sn-Doped Hematite Nanoflakes by Flame Annealing - Wang, Lei; Lee, Chong-Yong; Mazare, Anca Valentina; Lee, Kiyoung; Müller, Julian; Spiecker, Erdmann; Schmuki, Patrik (Chemistry - A European Journal, 2014)
The effect of flame annealing on the water-splitting properties of Sn decorated hematite (-Fe2O3) nanoflakes has been investigated. It is shown that flame annealing can yield a considerable enhancement in the maximum photocurrent under AM 1.5 (100mWcm(-2)) conditions compared to classic furnace annealing treatments. Optimizing the annealing time (10s at 1000 degrees C) leads to a photocurrent of 1.1mAcm(-2) at 1.23V (vs. RHE) with a maximum value 1.6mAcm(-2) at 1.6V (vs. RHE) in 1M KOH. The improvement in photocurrent can be attributed to the fast direct heating that maintains the nanoscale morphology, leads to optimized Sn decoration, and minimizes detrimental substrate effects.
Keywords: doping; hematite nanoflakes; water splitting

Hierarchical decoration of anodic TiO2 nanorods for enhanced photocatalytic degradation properties - Tsui, Lok-Kun; Nguyen, Nhat Truong; Wang, Lei; Kirchgeorg, Robin; Zangari, Giovanni; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work vertically aligned TiO2 nanorods were fabricated by anodization of Al/Ti dual layer structures. Anodization of Al leads to the formation of a porous alumina layer which is used as a template for the growth of TiO2 nanorods. We have studied the characteristics of these nanorods after annealing by high resolution TEM, showing a core–shell structure along the length of the nanorods formed from the expansion of the TiO2 nanorod into the alumina template during growth. Modification of the nanorods by spin coating of a solution of titanium isopropoxide (TIPO) in isopropanol yields enhanced photocatalytic activity up to 12 times due to the increase in surface area, light absorption volume, and the creation of a crystalline coating with an anatase-phase.
EAM Import::2019-03-13

Hydrothermal growth of highly oriented single crystalline Ta2O5 nanorod arrays and their conversion to Ta3N5 for efficient solar driven water splitting - Su, Zixue; Wang, Lei; Grigorescu, Sabina Georgiana; Lee, Kiyoung; Schmuki, Patrik (Chemical Communications, 2014)
We grow vertically aligned single crystalline Ta2O5 nanorod arrays that can be converted to Ta3N5 nanorod arrays by nitridation. Combined with cobalt phosphate (Co-Pi) as a co-catalyst, such Ta3N5 nanorod photoanodes can yield photocurrent densities of ∼3.6 mA cm-2 at 1.23 VRHE and ∼8.2 mA cm-2 at 1.59 VRHE under AM 1.5G (100 mW cm-2) irradiation.
EAM Import::2019-03-13

Improved photoelectrochemical water splitting of hematite nanorods thermally grown on Fe–Ti alloys - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Electrochemistry Communications, 2014)
Here we show that hematite ( extgreeka-Fe2O3) nanostructures with a high water splitting performance can be formed on Fe–Ti alloys using the most simple thermal treatment in air and Ar. The use of the Fe–Ti alloy suppresses the formation of thick suboxide underlayers that are strongly detrimental for the photoconversion efficiency. The formed nanorod structures show an onset potential of up to 0.6–0.7 VRHE. This beneficial effect is attributed to the combination of suppression of a thick suboxide and the nature of the extgreeka-Fe2O3 nanorods after Ar annealing.
EAM Import::2019-03-13

Si-doped Fe2O3 nanotubular/nanoporous layers for enhanced photoelectrochemical water splitting - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2013)
The present work reports the enhancement of the photoelectrochemical water splitting performance of in-situ silicon (Si)-doped nanotubular/nanoporous (NT/NP) layers. These layers were grown by self-organizing anodization on Fe-Si alloys of various Si content. The incorporation of Si is found to retard the layer growth rates, leads to a more pronounced nanotubular morphology, and most importantly, an improved photoelectrochemical behavior. By increasing Si content from 1, 2 to 5 at.% in the iron oxide NT/NP photoanodes, the photocurrent onset potential shifts favorably to lower values. At 1.3 V vs. RHE, hematite layer with 5 at.% Si shows a 5-fold increase of the photocurrent, i.e. 0.5 mA cm- 2 in comparison to 0.1 mA cm- 2 for the undoped samples. The study also reveals that a suitable layer thickness is essential to achieve a beneficial effect of the Si doping.
EAM Import::2019-03-13

Solar water splitting: preserving the beneficial small feature size in porous α-Fe2O3 photoelectrodes during annealing - Wang, Lei; Lee, Chong-Yong; Schmuki, Patrik (Journal of Materials Chemistry A, 2012)
We prepared mesoporous extgreeka-Fe2O3/FTO electrodes by a simple anodic precipitation and annealing method. The classic problem is that when annealed in air at >500 °C, the individual particle size increases from ≈20 nm to 40–60 nm. This grain growth is highly detrimental for the water splitting efficiency. In the present work we show that grain coarsening can efficiently be prevented by a two-step annealing method in Ar, leading to photocurrent densities for such electrodes (obtained in 1 M KOH solution) of up to 2.6 mA cm-2 at 1.6 V vs. RHE under AM 1.5 100 mW cm-2 illumination, which is significantly higher than 1.5 mA cm-2 for conventionally annealed samples.
EAM Import::2019-03-13

Tantalum Nitride Nanorod Arrays: Introducing Ni–Fe Layered Double Hydroxides as a Cocatalyst Strongly Stabilizing Photoanodes in Water Splitting - Wang, Lei; Dionigi, Fabio; Nguyen, Nhat Truong; Kirchgeorg, Robin; Gliech, Manuel; Grigorescu, Sabina Georgiana; Strasser, Peter; Schmuki, Patrik (Chemistry of Materials, 2015)
Ta3N5 nanostructures are widely explored as anodes for photoelectrochemical (PEC) water splitting. Although the material shows excellent semiconductive properties for this purpose, the key challenge is its severe photocorrosion when used in typical aqueous environments. In the present work we introduce a NiFe layered double hydroxide (LDH) cocatalyst that dramatically reduces photocorrosion effects. To fabricate the Ta3N5 electrode, we use through-template anodization of Ta and obtain oxide nanorod arrays that then are converted to Ta3N5 by high temperature nitridation. After modification with our cocatalyst system, we obtained solar photocurrents of 6.3 mA cm–2 at 1.23 VRHE in 1 M KOH, and an electrode maintains about 80% of the initial activity for extended irradiation times.
EAM Import::2019-03-12

Tungsten doping of Ta3N5-nanotubes for band gap narrowing and enhanced photoelectrochemical water splitting efficiency - Grigorescu, Sabina Georgiana; Bärhausen, Benedikt; Wang, Lei; Mazare, Anca Valentina; Yoo, Jeong Eun; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2015)
Ordered W-doped Ta2O5 nanotube arrays were grown by self-organizing electrochemical anodization of TaW alloys with different tungsten concentrations and by a suitable high temperature ammonia treatment, fully converted to W:Ta3N5 tubular structures. A main effect found is that W doping can decrease the band gap from 2 eV (bare Ta3N5) down to 1.75 eV. Ta3N5 nanotubes grown on 0.5 at.% W alloy and modified with Co(OH)x as co-catalyst show 33% higher photocurrents in photoelectrochemical (PEC) water splitting than pure Ta3N5.
EAM Import::2019-03-13